Abstinence phenomena of chronic cannabis-addicts prospectively monitored during controlled inpatient detoxification (Part II): Psychiatric complaints and their relation to delta-9-tetrahydrocannabinol and its metabolites in serum. (1st October 2015) - Bonnet, Udo; Borda, Thorsten; Scherbaum, Norbert; Specka, Michael
Highlights: Cannabis inpatient detoxification treatment is markedly effective on psychiatric symptoms. Global scores of SCL-90-R decreased with Cohen's d  = 0.8–0.9 from admission to day 16. Serum levels of THC predicted cognitive impairment and motor retardation. Cannabis "amotivational syndrome" is based on prolonged cannabis intoxication. Abstract: Objective: To investigate the impact of inpatient detoxification treatment on psychiatric symptoms of chronic cannabis addicts and to analyze the influence of serum cannabinoid levels on the severity of these symptoms. Methods: Thirty five treatment-seeking, not active co-morbid chronic cannabis dependents (ICD-10) were studied on admission and on abstinence days 8 and 16, using several observational and self-report scales, such as Hamilton Depression Rating Scale (HAMD), Hamilton Anxiety Rating Scale (HAMA), Young Mania Rating Scale (YMRS) and Brief Psychiatric Rating Scale (BPRS), and the Symptom Checklist-90-Revised (SCL-90-R). Simultaneously obtained serum was analyzed with regard to levels of delta-9-tetrahydrocannabinol (THC) and its main metabolites 11-hydroxy-delta-9-tetrahydrocannabinol (THC-OH) and 11-nor-delta-9-tetrahydrocannabinol-9-carboxylic acid (THC-COOH). Results: At admission, nearly 90% of the patients were not, or only mildly, affected by depression, anxiety or manic symptoms. In contrast, patients' self-description indicated a strong psychiatric burden in approximately 60% of the cases. All patients improved significantly within 16 days of the treatment. Effect sizes ranged from 0.7 to 1.4. (Cohen's d ) for the respective scales. Serum THC-levels were positively associated with impairment of cognition in HAMA and motor retardation in BPRS. All other test results were not significantly related to the serum levels of the measured cannabinoids. Discussion: Effects of the cannabis withdrawal syndrome and executive dysfunctions might explain the discrepancy between the observer ratings and self-reported psychiatric burden. Conclusion: Inpatient cannabis detoxification treatment significantly improved psychiatric symptoms. Serum THC-levels were not associated with affective symptoms and anxiety but predicted cognitive impairment and motor retardation.